2022
DOI: 10.3390/diagnostics12020393
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Surrogate Virus Neutralization Test Based on Antibody-Mediated Blocking of the Interaction of ACE2 and SARS-CoV-2 Spike Protein RBD

Abstract: The humoral response to the SARS-CoV-2 S protein determines the development of protective immunity against this infection. The standard neutralizing antibodies detection method is a live virus neutralization test. It can be replaced with an ELISA-based surrogate virus neutralization test (sVNT), measuring the ability of serum antibodies to inhibit complex formation between the receptor-binding domain (RBD) of the S protein and the cellular ACE2 receptor. There are conflicting research data on the sVNT methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Note that recently our compatriots, D. Kolesov et al [ 14 ], published work similar to that presented here. Their study was also performed on the Moscow population and with the participation of patients who had been infected with Wuhan or similar variants of SARS-CoV-2 [ 14 ]. However, in our study, we obtained lower correlation coefficients between the results of cVNT, sVNT, and the anti-RBD test.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Note that recently our compatriots, D. Kolesov et al [ 14 ], published work similar to that presented here. Their study was also performed on the Moscow population and with the participation of patients who had been infected with Wuhan or similar variants of SARS-CoV-2 [ 14 ]. However, in our study, we obtained lower correlation coefficients between the results of cVNT, sVNT, and the anti-RBD test.…”
Section: Discussionsupporting
confidence: 82%
“…Notably, the largest number of such patients ( n = 23) was detected using sVNT, a test that detects only RBD-neutralizing antibodies. It can be assumed that some plasma samples from this group of recovered patients contained neutralizing antibodies that bind to the S protein outside the RBD region [ 14 ]. Indeed, it has been previously shown that antibodies to the N-terminal domain or the S2 region of the S-protein can also be involved in the neutralization of the virus [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular domain of the human angiotensin-converting enzyme 2 (residues 319–541) was fused to an immunoglobulin G crystallizable fragment (ACE2-Fc) as described earlier [ 16 ]. The ACE2-Fc was stably expressed in a DHFR-negative Chinese hamster ovary (CHO) DG-44 cell line (Thermo Fischer Scientific, Waltham, MA, USA) and was purified from the conditioned-culture medium using chromatography on MabSelect SuRe column (Cytiva, Marlborough, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In 2022, Kolesov et al [15] published a simpler version allowing reaction in the ELISA plates, where the coating agent was the RBD viral protein while ACE2 was the reactant in the enyme conjugate. A third version may appear in the future, where the reactant in the detecting enzyme conjugate is replaced with a polyclonal, or alternatively a monoclonal, speci c viral antibody.…”
Section: The Blocking Antibody Elisamentioning
confidence: 99%